Luminescent [ZnIILnIII] complexes anchored on graphene: Synthesis and crystal structures of [ZnIIEuIII] and [ZnIITbIII] complexes decorated with pyrene groups. (16th December 2020) - Apostol, Adrian A.; Mihalache, Iuliana; Mocanu, Teodora; Tutunaru, Oana; Pachiu, Cristina; Gavrila, Raluca; Maxim, Catalin; Andruh, Marius
Abstract : Two [ZnLn] heterobinuclear complexes decorated with pyrene groups, [ZnEu(valpn)(hfac)2 (pb)], have been obtained, in order to be deposited on graphene (Ln III Eu III 2a ; Tb III 2b ); H2 valpn is the Schiff base compartmental ligand resulted from the condensation reaction between o ‐vanillin and propylenediamine (Hpb = 1‐pyrenebutiric acid; Hhfac = hexafluoroacetylacetone). The two complexes have been obtained by replacing the acetato ligand in [ZnEu(valpn)(hfac)2 (CH3 COO)] (Eu III : 1a ; Tb III : 1b ) by pb − anions. The crystal structures of 1a, 2a, and 2b have been solved and described. Compounds 2a and 2b were grafted on monolayer graphene/quartz. The new hybrid materials, 2a/graphene and 2b/graphene, as well as the starting complexes are luminescent. The two hybrid materials have been characterized by Raman spectroscopy, atomic force microscopy (AFM), and scanning electron microscopy (SEM) measurements, which confirm the presence of the complexes on graphene. Abstract : Two [ZnLn] heterobinuclear complexes decorated with pyrene groups have been grafted on graphene via π–π stacking interactions established between the pyrene moieties and graphene (LnEu and Tb). The two new complexes as well the hybrid materials show the characteristic red and, respectively, green luminescence.